Trust and Mistrust in the Economies of the China-Russia Borderlands - Humphrey, Caroline (Amsterdam University Press, 2018)
This book focuses on northeast Sino-Russian border economies and how trans-border economies function in practice, often across great distances, despite widespread mistrust.